Age-associated SARS-CoV-2 breakthrough infection and changes in immune response in a mouse model. Issue 1 (31st December 2022) - Chen, Yanxia; Li, Can; Liu, Feifei; Ye, Zhanhong; Song, Wenchen; Lee, Andrew C. Y.; Shuai, Huiping; Lu, Lu; To, Kelvin Kai-Wang; Chan, Jasper Fuk-Woo; Zhang, Anna Jinxia; Chu, Hin; et al.
ABSTRACT: Older individuals are at higher risk of SARS-CoV-2 infection and severe outcomes, but the underlying mechanisms are incompletely understood. In addition, how age modulates SARS-CoV-2 re-infection and vaccine breakthrough infections remain largely unexplored. Here, we investigated age-associated SARS-CoV-2 pathogenesis, immune responses, and the occurrence of re-infection and vaccine breakthrough infection utilizing a wild-type C57BL/6N mouse model. We demonstrated that interferon and adaptive antibody response upon SARS-CoV-2 challenge are significantly impaired in aged mice compared to young mice, which results in more effective virus replications and severe disease manifestations in the respiratory tract. Aged mice also showed increased susceptibility to re-infection due to insufficient immune protection acquired during the primary infection. Importantly, two-dose COVID-19 mRNA vaccination conferred limited adaptive immune response among the aged mice, making them susceptible to SARS-CoV-2 infection. Collectively, our findings call for tailored and optimized treatments and prevention strategies against SARS-CoV-2 among older individuals.